Mummies in nineteenth century America : ancient Egyptians as artifacts - Wolfe, S. J., 1951- (McFarland & Co., 2009)
"This work examines Egyptian mummies as artifacts in pre-1900 America--how they got here, what happened to them, and how they were perceived. Collected newspaper accounts and other documents reveal the progression of American interest in mummies. Numerous mummies are identified, and commentary on mummy coffins and discussion of methods of public exhibition are included" -- Provided by publisher.